(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Introduction: The ABO blood group system was the first human blood group system to be discovered by Karl Landsteiner in 1900. Next to ABO, Rhesus system the second most significant blood group system. Blood group is applied to the genetically determined antigen which can be detected on the red cell surface of an individual by specific antibody. The aim of this study to examine the distribution patterns of ABO and Rh-D blood group among the blood donor attending at Transfusion Medicine Department in CMOSH. It is helpful to increase social awareness among the population and maintain safe blood transfusion to patient. Materials and methods: It was a cross sectional study conducted in the Department of Transfusion Medicine,Chattagram Maa O Shishu Hospital Medical College, from January to December 2022. After proper ethical consideration a total of 7,289 blood donors were included in this study. ABO and Rh blood groupings were carried out in our blood bank by standard tile techniques. Results: Among 7,289 blood donors male blood donors were 6,936(95.15%), female blood donors were 353(4.84%).2,775 (38.07%) blood donor were identified as having blood group B while 2,185 (29.97%) were blood group O, 1702( 23.35%) and 627(8.6%)were blood group A and AB respectively. Rh-D positive were 6,960(95.48%) and Rh-D negative were 329(4.51%). Conclusion: The knowledge of ABO and Rhesus D blood group is important in blood transfusion service.Study of blood grouping not only generates a simple database but also create a great social awareness about self-blood grouping and safe blood transfusion among the population of a country. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 52-55